2007
DOI: 10.1158/1541-7786.mcr-06-0321
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the EGFR Gene Target EphA2 Inhibits Epidermal Growth Factor–Induced Cancer Cell Motility

Abstract: EphA2 overexpression has been reported in many cancers and is believed to play an important role in tumor metastasis and angiogenesis. We show that the activated epidermal growth factor receptor (EGFR) and the cancer-specific constitutively active EGFR type III deletion mutant (EGFRvIII) induce the expression of EphA2 in mammalian cell lines, including the human cancer cell lines A431 and HN5. The regulation is partially dependent on downstream activation of mitogen-activated protein kinase/extracellular signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
118
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 45 publications
9
118
1
Order By: Relevance
“…c-Cbl has been reported to participate in EphA receptor degradation induced by ligand stimulation (Walker-Daniels et al, 2002;Wang et al, 2002;Sharfe et al, 2003). Larsen et al, 2007 showed that other than transcriptional target of EGFR, EphA2 colocalized with activated EGFR. Thus, recruitment of c-Cbl by activated EphA receptor upon ligand binding potentially facilitates its access to EGFR, and promotes subsequent ubiquitylation of the receptor, which could interpret the potential role of Eph forward signaling.…”
Section: Discussionmentioning
confidence: 99%
“…c-Cbl has been reported to participate in EphA receptor degradation induced by ligand stimulation (Walker-Daniels et al, 2002;Wang et al, 2002;Sharfe et al, 2003). Larsen et al, 2007 showed that other than transcriptional target of EGFR, EphA2 colocalized with activated EGFR. Thus, recruitment of c-Cbl by activated EphA receptor upon ligand binding potentially facilitates its access to EGFR, and promotes subsequent ubiquitylation of the receptor, which could interpret the potential role of Eph forward signaling.…”
Section: Discussionmentioning
confidence: 99%
“…EphA2 knockout mice were shown to be very susceptible to DMBA/ TPA-induced skin carcinogenesis (25). Further, activation of EPHA2 by its ligand EFNA1 or small molecule induced activation of EPHA2 reduces cell proliferation and cell motility and suppresses integrin function, suggesting its tumor-suppressive function (26)(27)(28). Our high-throughput approach identified EphA2 as a prime tumor suppressor candidate, and we hypothesized that, if deleted in a tumor cell-specific manner, EphA2 would function as a KRas G12D -cooperative tumor suppressor in lung adenocarcinoma.…”
mentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35] Yet, there is also some evidence that EphA2 may function as a tumor suppressor, as activation of EphA2 receptors following ligand binding has been shown to lead a reduction in cell growth that is associated with inhibition of the RAS/MAPK pathways, and EphA2 2/2 gene trap mice demonstrate increased susceptibility to skin carcinogenesis. [36][37][38][39] Further, EphA2 has been reported to be a transcriptional target of the p53 tumor suppressor, 40 and expression of EphA2 was shown to negatively affect the proliferation and promote apoptosis in lung and breast cancer cells.…”
mentioning
confidence: 99%
“…41,42 This is further supported by adenoviral vector delivery of EphrinA1 and EphA2 activating antibodies that inhibit malignant cell behavior. 24,34,36 Independent of ligand binding, phosphorylation of EphA2, both autophosphorylation and phosphorylation by other receptor tyrosine kinases (RTKs) may play a critical role in EphA2's oncogenicity. In some breast cancer cells, overexpression of wildtype EphA2 leads to constitutive phosphorylation of the receptor while EphA2 mutants that lack either the cytoplasmic domain or a kinase-dead point mutant (D738N) act in a dominant negative fashion to inhibit both receptor phosphorylation and endogenous receptor signaling, such as through the RAS/MAPK pathways.…”
mentioning
confidence: 99%